Manhaj Bahsul Masail Menurut Nahdatul Ulama (Nu) - Darmawati Darmawati (Sulesana, 2011)
Nahdlatul Ulama that abbreviated as NU, is one of the largest organizations in Indonesia today. The organization is engaged in education, preaching and welfare-social well-being. Established by KH. Muhammad Hashim Asy'ari and fully supported by the scholars boarding school caretakers, especially in Java. As background the formation of this organization is in connection with the rejection of clerical delegates Indonesia by King Saud, in a meeting held in Saudi Arabia, by reason of the clergy do not have the organization. There are four methods used Bahsul Masail, can be sorted as follows first, taking the law qaul (opinion of Imam sect) or face (opinion followers of sects) is the primary method of jurisprudence concerning the law, by referring directly to the texts of books or book-sect priest book compiled by the followers of four sects. This is then called a method qauli. Second, if it can not be referred to the books, then ditempulah ilhaq step Namely associate a new problem with which there is no law provisions. Third, if those two things can not be digunkana, then used the following methods manhaji istinbat of the four schools of law. Fourth, if the method can be performed manhaji No, it had to be done talfiq. Talfiq this as the final step for a while in the workings of Bahsul Masail.